2021
DOI: 10.1021/acssuschemeng.1c00536
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Based Single-Atom Catalyst toward Triiodide Reduction Reaction in Hybrid Photovoltaics

Abstract: It is very significant to obtain highly efficient, costeffective, and durable electrocatalysts toward triiodide reduction reaction (TRR) in hybrid photovoltaics. In this study, a nickelbased single-atom catalyst (SAC) (Ni-SAC) was prepared by the facile carbonization of NiPc@ZIF-8 and explored as a highly efficient Pt-free catalyst for TRR. During the carbonization process, the Ni species were separated by coordinate nitrogen atoms and distributed homogeneously within the porous carbon matrix, with the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…X-ray diffraction (XRD) patterns of the Mo–N–C sample only presented a broad diffraction peak at 43.2°, extremely similar to that of the reference N–C sample (Figure S2). No other peaks from oxides and metal were detected, indicating no formation of other Mo-related NPs.…”
Section: Results and Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…X-ray diffraction (XRD) patterns of the Mo–N–C sample only presented a broad diffraction peak at 43.2°, extremely similar to that of the reference N–C sample (Figure S2). No other peaks from oxides and metal were detected, indicating no formation of other Mo-related NPs.…”
Section: Results and Discussionmentioning
confidence: 95%
“…High-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM) images revealed that the as-obtained Mo−N−C sample presented rhombic dodecahedral morphologies (Figure 1b,c), which are similar to those observed from the reference N−C sample S2). 34 No other peaks from oxides and metal were detected, indicating no formation of other Mo-related NPs. Furthermore, Raman spectra revealed that the N-doped carbon support has abundant defects in the Mo−N−C and N− C catalysts (Figure S3).…”
Section: Preparation and Characterization Of The Single-atom Catalystmentioning
confidence: 96%
See 2 more Smart Citations
“…However, due to the poor electrical and ionic conductivity, the overall performance is rather low. To alleviate this problem, NiO nanoparticles have been combined with several conductive materials. Carbon materials demonstrated a potential ability to enhance the conductivity of NiO and hence the overall performance of DSSC via the synergistic effect . Recently, a NiO-multiwalled carbon nanotubes (MWCNTs) composite was prepared and utilized as CE for DSSCs, the assembled device exhibited a PCE of 3.80% .…”
Section: Introductionmentioning
confidence: 99%